Relokasi Hiposenter Gempa Bumi dan Model Struktur Kecepatan 1 Dimensi Gelombang P dengan Menggunakan Metode Coupled Velocity – Hypocenter di Daerah Sulawesi Tengah dan Sekitarnya - Lusti Nur Azizah; Arif Tjahjono; Agung Sabtaji (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2019)
Sulawesi Island is composed of complex tectonic arrangements. Most earthquake activities in Sulawesi are affected by the Palu - Koro Fault and Matano Fault. Palu - Koro Fault and Matano Fault are one of the faults in Central Sulawesi. Active movement of the fault results in high earthquake activity in the region of Central Sulawesi and its surroundings. This makes the importance of earthquake parameters in Central Sulawesi and surrounding areas. One of the efforts to find out earthquake parameter information accurately is to relocate. The purpose of this study was to conduct hypocenter earthquake relocation and determine the 1-D velocity structure of P waves in Central and surrounding areas using the Coupled Velocity - Hypocenter method with Velest 3.3 software. The data used are tectonic earthquake data from November 2009 to March 2018, data recording stations, and initial speed data. The results of data processing using the Velest 3.3 software are that some of the results of the relocation are close to fault, the final Vp at a depth of 9 km is slower than the initial Vp, the correction of the station obtained in this calculation is in the interval -0.81 to +0.54.